PENGELOLAAN HUTAN NAGARI BERDASARKAN SKEMA PERHUTANAN SOSIAL OLEH MASYARAKAT HUKUM ADAT DI PROPINSI SUMATERA BARAT - Syofiarti Syofiarti; Titin Fatimah; Kevin Muhammad Yades (Program Magister Ilmu Hukum Universitas Ekasakti, 2023)
Forests are one of the natural resources that are used by communities around the forest to support their lives, including the Indigenous Peoples. However, in forest utilization various tenure conflicts are often encountered, such as claims over forest areas. Forest management by communities living around the forest is often in conflict with government policies. After the issuance of the Constitutional Court Decision No.35/PUU-X/2012 it was a form of acknowledgment of Indigenous Peoples in managing forests and designating customary forests as forests within the territory of Indigenous Peoples. In line with the Constitutional Court's decision, the government then launched a Social Forestry program in order to improve people's welfare through forest management. One of the Social Forestry schemes that is the focus of this research is the management of Village Forests (Nagari Forest), which in this case is given to the Indigenous Peoples. There is still a delay in the management permit process because it has to be submitted to the Ministry. Besides that, there are still various tenurial conflicts in forest areas. Based on what was stated, the researcher is interested in examining how the management of Nagari Forest is based on the Social Forestry scheme by Indigenous Peoples, how is the licensing and management of Nagari Forest based on the Social Forestry scheme by Indigenous Peoples, and formulating a pattern of managing Nagari Forest based on the Social Forestry scheme by Indigenous Peoples.